2009
DOI: 10.1038/mp.2009.125
|View full text |Cite
|
Sign up to set email alerts
|

Novel loci for major depression identified by genome-wide association study of Sequenced Treatment Alternatives to Relieve Depression and meta-analysis of three studies

Abstract: We report a genome-wide association study (GWAS) of major depressive disorder (MDD) in 1,221 cases from the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study and 1,636 screened controls. No genome-wide evidence for association was detected. We also carried out a meta-analysis of three European-ancestry MDD GWAS datasets: STAR*D, Genetics of Recurrent Early-Onset Depression (GenRED) and the publicly-available Genetic Association Information Network MDD dataset (GAIN-MDD). These datasets, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
172
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(181 citation statements)
references
References 61 publications
4
172
3
2
Order By: Relevance
“…However, this finding was not replicated by Shyn et al on a different cohort of European ancestry [37]. Differences in inclusion criteria may be crucial in these different findings.…”
Section: Genetic Techniques To Detect Variantscontrasting
confidence: 51%
“…However, this finding was not replicated by Shyn et al on a different cohort of European ancestry [37]. Differences in inclusion criteria may be crucial in these different findings.…”
Section: Genetic Techniques To Detect Variantscontrasting
confidence: 51%
“…Indeed, genome‐wide association studies (GWAS) have shown that these disorders are highly polygenic (Barnett & Smoller, 2009; Schizophrenia Working Group of the Psychiatric Genomics, 2014; Shyn et al., 2011) with many genes exerting their influence on numerous neural pathways involved in complex aspects of brain function and likely being impacted upon by environmental events. It has been proposed that individual vulnerability and sensitization to the later development of mental health disorders may partly be regulated through variation in genes encoding proteins that impact on neurotransmitter and hormone systems such as those involved in dopamine, serotonin, and cortisol function (Caspi & Moffitt, 2006; Collip, Myin‐Germeys, & Van Os, 2008; van Winkel, Stefanis, & Myin‐Germeys, 2008; van Winkel, van Nierop, Myin‐Germeys, & van Os, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of large genome-wide association studies, and some subsequent meta-analyses, have identified genetic polymorphisms associated with both risk of depression [71][72][73] and response to antidepressant therapy. 74,75 However, these studies have been unable to demonstrate consistent and reproducible genetic associations.…”
Section: Folate Depression and Geneticsmentioning
confidence: 99%